1995
DOI: 10.1029/95jd00510
|View full text |Cite
|
Sign up to set email alerts
|

On the lack of southern hemisphere polar mesosphere summer echoes

Abstract: We report VHF radar observations of the southern high‐latitude mesopause region using wind profilers that were installed recently on King George Island, Antarctica, and Ushuaia, Argentina. Briefly, our observations, which were made during January and February 1993, show almost no evidence of so‐called polar mesosphere summer echoes, or PMSE. Since these echoes are a predominant feature of the northern high‐latitude mesosphere in summer, their absence in the southern hemisphere is both surprising and intriguing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 21 publications
0
28
1
Order By: Relevance
“…We concluded that Antarctic P MSEs, if they existed at all, had to be at least 34 to 44 dB weaker than their Northern Hemispheric counterparts. We also reported, as the note added in proof in our previous study [Balsley et al, 1995], that a more thorough analysis of the first year's using refined noise reduction techniques yielded one very weak PMSE return that lasted for a few hours.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…We concluded that Antarctic P MSEs, if they existed at all, had to be at least 34 to 44 dB weaker than their Northern Hemispheric counterparts. We also reported, as the note added in proof in our previous study [Balsley et al, 1995], that a more thorough analysis of the first year's using refined noise reduction techniques yielded one very weak PMSE return that lasted for a few hours.…”
Section: Introductionmentioning
confidence: 89%
“…Until January 15, 1994, the radar system employed at the Machu Picchu site during both the 1992-1993 and the 1993-1994 campaigns was the same system reported by Balsley et al [1995]. This early system used a single system that was switched manually between three antennas fixed to point to the vertical and to 15 ø off vertical toward the north and east [Sarango et al, 1994].…”
Section: Radar System and Operationsmentioning
confidence: 99%
“…One reason proposed for the weaker and more sporadic PMSE returns in the southern hemisphere is that the summer upper mesospheric temperatures in that hemisphere are somewhat warmer [Balsley et al, 1995;Hall, 1995;Woodman et al, 1999]. Verification of this idea is difficult, since, until recently, only a few studies of high-latitude summertime upper mesospheric temperatures in the two hemispheres have been published [Labitzke and Barnett, 1981;Barnett and Comey, 1985;Thomas, 1995].…”
Section: Observations Of Pmse (Polar Mesospherementioning
confidence: 99%
“…Since the initial report of PMSE, similar echoes have been detected at mid-latitudes (Reid et al, 1989;Thomas et al, 1992), and at Southern polar latitudes (Woodman et al, 1999). However, there is a disparity in the amount of PMSE activity observed at southern latitudes compared with northern latitudes (Balsley et al, 1995). During the ensuing years, a rich body of literature has developed in an attempt to explain PMSE, among which are several review papers (Röttger et al, 1988;Cho and Kelley, 1993;Cho and Röttger, 1997).…”
Section: Introductionmentioning
confidence: 99%